The effect of 8 weeks of circuit training on body weight, blood pressure, serum Cholesterol levels and liver enzymes in elderly women with metabolic syndrome - Zahra Nourollahi; Vahid Valipour Dehnou; Rasoul Eslami (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2019)
Introduction: Inactive lifestyle is a very important risk factor for the development of many diseases, including metabolic syndrome. In aging, in addition to aging-related problems, some elderly people develop metabolic syndrome, which is more common in women than men. The metabolic conditions of the body play a major role in the emergence and progression of this disease. This study was performed with aim to investigate the effect of 8 weeks of circuit training on body weight, blood pressure and Cholesterol levels and liver enzymes in elderly women with metabolic syndrome in Khorramabad city. Methods: This semi-experimental study was performed in 2017 on 18 elderly women with metabolic syndrome at Farzanegan rehabilitation center in Khorramabad. During the daily routine activities, the subjects participated in 8-week circuit training protocol which performed 3 sessions per week. The fasting blood sample was taken from the subjects 24 hours before the training protocol and 48 hours after the training protocol. Body weight, blood pressure, serum cholesterol and liver enzymes were measured. Data was analyzed by SPSS software (version 24) and Kolmogrov-Smirnov and correlated t-test. PResults: The results showed a significant decrease in serum AST (p =.043) and cholesterol (p =.033) levels, systolic blood pressure (p =0.001) and body weight (p =0.001) and BMI (p=0.001), and non-significant decrease in serum levels of ALT (p =0.487) in comparison with pre-test values in elderly women with metabolic syndrome. Conclusion: The circuit training in elderly women with metabolic syndrome has beneficial effects on serum concentration of AST, ALT and cholesterol; also it reduces systolic blood pressure and body weight, therefore can promote their health.